Performances of Injustice : the politics of truth, justice and reconciliation in Kenya / Gabrielle Lynch. - Lynch, Gabrielle (Cambridge University Press, 2018)
Following unprecedented violence in 2007/8, Kenya introduced two classic transitional justice mechanisms: a truth commission and international criminal proceedings. Both are widely believed to have failed, but why? And what do their performances say about contemporary Kenya; the ways in which violent pasts persist; and the shortcomings of transitional justice? Using the lens of performance, this book analyses how transitional justice efforts are incapable of dealing with how unjust and violent pasts actually persist. Gabrielle Lynch reveals the story of an ongoing political struggle requiring substantive socio-economic and political change that transitional justice mechanisms can theoretically recommend, and which they can sometimes help to initiate and inform, but which they cannot implement or create, and can sometimes unintentionally help to reinforce.